2012
DOI: 10.21236/ada585672
|View full text |Cite
|
Sign up to set email alerts
|

Combining Psychological Models with Machine Learning to Better Predict People's Decisions

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Creating agents that pro¯ciently interact with people is critical for many applications. Towards creating these agents, models are needed that e®ectively predict people's decisions in a variety of problems. To date, two appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…On a broader note, we hope to further the development of a synergistic correspondence between psychology and data science approaches in scientific modeling (Rosenfeld, Zuckerman, Azaria, & Kraus, 2012;Dwyer, Falkai, & Koutsouleris, 2018;Bourgin, Peterson, Reichman, Griffiths, & Russell, 2019). Cognitive science famously grew out of the intersection of six different fields (Gardner, 1987), but some have suggested that this revolution did not create the SCIENTIFIC REGRET MINIMIZATION 26 emergence of a new discipline (Lakatos, 1986;Miller, 2003;Núñez et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…On a broader note, we hope to further the development of a synergistic correspondence between psychology and data science approaches in scientific modeling (Rosenfeld, Zuckerman, Azaria, & Kraus, 2012;Dwyer, Falkai, & Koutsouleris, 2018;Bourgin, Peterson, Reichman, Griffiths, & Russell, 2019). Cognitive science famously grew out of the intersection of six different fields (Gardner, 1987), but some have suggested that this revolution did not create the SCIENTIFIC REGRET MINIMIZATION 26 emergence of a new discipline (Lakatos, 1986;Miller, 2003;Núñez et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It has already been suggested that achieving successful human-machine collaboration requires the modeling of human behavior for predicting people's decisions [7,8]. It has been shown, for example, that information about drivers (i.e., driving style) improves the prediction models regarding the use of an automated assistive system [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the political sciences, decision trees have been used for modeling international conflicts and international negotiation (Druckman et al, 2006). Rosenfeld et al (2012) Table 1 psychology, used random forests to predict future suicide attempts of patients.…”
Section: Induction Of Decision Treesmentioning
confidence: 99%